Little shop of horrors [videorecording (Blu-Ray)] - Moranis, Rick; Greene, Ellen; Gardenia, Vincent; Martin, Steve, 1945-; Belushi, James, 1954-; Candy, John; Guest, Christopher; Murray, Bill, 1950 September 21-; Ashman, Howard; Ashman, Howard; Menken, Alan; Oz, Frank; et al. (Warner Home Video, 2017)
In this musical, Mushnik's Flower Shop houses an exotic potted plant called Audrey II. People are rushing in to see it but if they knew the truth, they would rush right out.